Going Feral: Authentica on the Edge of Australian Culture - St John, Graham (The Australian journal of anthropology, 1997)
In a study of an Australian ‘alternative lifestyle gathering’, I investigate the authentica (the multiplicity of discourse and practice valued as ‘true’, ‘natural’, ‘pure’) championed and performed on-site. Using emic description, the article details the authentica of ‘play’ (ludic exploration via alterity, especially indigeneity), ‘earth’ (ecological consciousness) and ‘tribe’ (the search for belonging in community) which are axiomatic to ConFest (Conference/Festival), one of Australia's principal sites for the celebration of alternative (‘edge’) culture. In this counter-space, an outsider status I call ‘ferality’ is conditioned. A repository of authenticity for many ConFesters, the ambivalent category feral, with its particular subcultural traits, is realised in a hyper-liminal zone on the margins, the cultural hinterland, of Australian society. Using the work of Turner (on ‘liminality’) and Maffesoli (on ‘neo-tribalism’), I seek to throw light on the (re)production of alternative culture in an analysis of an event where new frontiers in the fields of leisure, health, environment, religion and community are explored.